It Will Take a Global Movement to Curb Corruption in Health Systems; Comment on "We Need to Talk About Corruption in Health Systems" - Margot I. Witvliet (Kerman University of Medical Sciences, 2019)
Corruption in health systems is a problem around the world. Prior research consistently shows that corruption is detrimental to population health. Yet public health professionals are slow to address this complicated issue on a global scale. In the editorial entitled "We Need to Talk About Corruption in Health Systems" concern with the general lack of discourse on this topic amongst health professionals is highlighted. In this invited commentary three contributing factors that hamper public dialogue on corruption are discussed. These include (i) corrupt acts are often not illegal, (ii) government and medical professionals continued acceptance of corruption in the health systems, and (iii) lack of awareness within the general public on the extent of the problem. It is advocated that a global movement that is fully inclusive needs to occur to eradicate corruption.